How to deliver a TED talk : secrets of the world's most inspiring presentations - Donovan, Jeremey (New York : McGraw-Hill Education, 2014)
'REVISED AND EXPANDED NEW EDITION A step-by-step playbook showing anyone how to give the speech'of their lives,' based on intensive study of the most popular TED TalksTED is a nonprofit dedicated to Ideas Worth Spreading. What began in 1984 as a conference bringing together the thought leaders and luminaries from the worlds of technology, entertainment, and design in Long Beach, California, TED exploded in popularity and led to a second conference held in Edinburgh, Scotland, TEDGlobal. TED challenged the world's most fascinating thinkers and doers to give the speech'of their lives' in 18 minutes or less.With more than 100 specific tips--including ways to open with an explicit statement of audience benefits and frame your idea worth spreading as an action-outcome response to a question worth asking--How to Deliver a TED Talk helps you select your topic, craft your story, master your delivery, and refine your design. It is a complete guide to creating presentations that inspire.A TEDx organizer and speaker, Jeremey Donovan is Group Vice President of Marketing at Gartner Inc., the world's leading information technology research and advisory company with $1.6 billion in annual revenue'--
Content. Choosing an idea worth spreading ; Organizing your talk ; Telling your story ; Crafing your catchphrase ; Opening your talk ; Transitioning between parts of your talk ; Concluding your talk -- Delivery. Projecting emotion ; Enhancing your language ; Adding humor ; Mastering your verbal delivery ; Managing your nonverbal delivery ; Moving around the stage -- Design. Creationg inspiring slides ; Using video effectively ; Using props ; Using a lectern ; Dressing for success on stage -- The journey to the stage and beyond. Getting selected to give a TED talk ; Preparing without fear ; Being introduced effectively ; Helping your TED video go viral ; Stop reading and start speaking.
Includes bibliographical references and index.
Keywords: Business presentations; Public speaking; Business communication